Genetic Variation Analysis of katG Gene Sequence in Mycobacterium tuberculosis Using RFLP In Silico - Nurfalinda, Siti; Aulia, Ony Nattasha; Sirwati, Fadila; Alridho, Rezeki Rival; Achayar, Afifatul (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2024)
Tuberculosis (TB) is an infectious disease that is the leading cause of death in Indonesia. This infection is caused by Mycobacterium tuberculosis. In Indonesia in 2021, there were approximately 824,000 cases of TB. A total of 8,268 TB cases were associated with resistance of M. tuberculosis to anti-tuberculosis drugs (OAT). MDR-TB is a strain that is resistant to two of the most important anti-tuberculosis drugs in first-line TB therapy, namely Rifampicin (RIF) and Isoniazid (INH). The most common mechanism of INH resistance is the katG gene mutation, found (95%) at codon 315. In the katG gene there is a change in the amino acid Ser (AGC) → Thr (ACC). Genetic variation in a population will affect the survival ability of an individual. This study used BamHI restriction enzyme. This study aims to analyze genetic variation in the KatG gene sequence in M. tuberculosis NCBI popset 2363230696 by using RFLP in silico. The results showed that there were genetic variations in the KatG gene sequence and two allelic variations contained in 7 KatG gene sequences using the BamHI restriction enzyme. Key words : M. tuberculosis, BamHI, KatG , Genetic Variation, RFLP in silico.